Does Women’s Autonomy Matter on Attitude Towards Condom Use in Reducing Risk for HIV Infection Among Married Women in Ethiopia? - Ahmed M (Dove Medical Press, 2020)
Mohammed Ahmed,1 Abdu Seid2 1Department of Public Health, College of Health Science, Woldia University, Woldia, Ethiopia; 2Department of Midwifery, College of Health Science, Woldia University, Woldia, EthiopiaCorrespondence: Mohammed Ahmed Email mohaasrar12@gmail.comBackground: Condom utilization remains as the forefront guard to reduce the HIV/AIDS pandemic. However, evidence showed that the dynamics of gendered power, beliefs, and attitudes about condoms and sexuality retards condom use for a large proportion of Africa’s people. Therefore, this study aimed to assess the association between women’s autonomy in health decision making and attitude to condom use in reducing risk for HIV in Ethiopia using a nationally representative, population-based household survey data.Methods: A cross-sectional study was carried out using 2016 nationally representative, population-based Ethiopia Demographic and Health Survey. SPSS version 21 was used to analyze the data. Multivariate logistic regression analysis was performed to assess the association between women’s autonomy in health decision making and attitude to condom use by controlling confounders. To declare statistically significant associations, adjusted odds ratios (AOR) with 95% confidence interval (CI) were used.Results: The present study enrolled 6787 weighted samples of married women. The study showed that the odds of attitude toward condom use were 1.39 times (AOR: 1.39; 95% CI: 1.04– 1.85) higher among women who decide for their health care compared to its counterparts. Also, the odds of attitude toward condom use were positively associated among women who conquered higher education (AOR: 1.97; 95% CI: 1.17– 3.33), who had the richest wealth index quintile (AOR: 1.45; 95% CI: 1.01– 2.07), and who had ever been tested for HIV (AOR: 1.31; 95% CI: 1.09– 1.57). However, the odds of attitudes toward condom use were negatively associated among Muslims (AOR: 0.58; 95% CI: 0.46– 0.74) and Protestant religion (AOR: 0.69; 95% CI: 0.54– 0.88) followers.Conclusion: The study culminates that women’s autonomy in health decision making improves attitudes toward condom use during sex for HIV prevention in Ethiopia. Besides, women’s higher education gets better wealth index, and HIV testing perks up the attitudes toward condom use; but religious affiliation deters it. Therefore, efforts need to be done in promoting women’s autonomy along with empowering women in education, economic as well as HIV detection. Furthermore, designing interventions that address primary prevention strategies like using condoms consistently along with addressing religious affiliation can have a significant effect on curtailing HIV/AIDS scourge.Keywords: women, autonomy, attitude, condom, HIV, Ethiopia